Foto Antwerpen 2005. - Pateer, Isabelle; Ruys, Christoph; FotoMuseum Provincie Antwerpen, Antwerpen (Antwerpen : FotoMuseum Provincie Antwerpen, 2005)
Felvégi, Andrea ; Provins, Marc ; Verherbrugge, Jan-Willem ; uit den Bogaard, Martijn ; Wuyts, Hans ; Konrad, Aglaia ; Bauwens, Nicole ; Laakso, Marku ; Dahlsten, Annika ; Ruegg, Ilone ; et al.
FotoMuseum Provincie Antwerpen, Antwerpen, 15.10 - 26.11.2005 / verschillende galerijen en instituten in Antwerpen, 15.10 - 26.11.2005
kunstcatalogus